MORPHOLOGICAL TYPOLOGY OF LIVESTOCK TERMINOLOGY IN THE ENGLISH LANGUAGE - Mukhamadiev Sukhrob Bakhtiyor ugli (Western European Studies, 2025)
The study of the morphological typology of livestock terminology in the English language focuses on the structural and word-formation mechanisms underlying terms related to animal husbandry. English livestock vocabulary demonstrates diverse morphological processes, including compounding (e.g., sheepfold, cattle-breeding), derivation (e.g., herdsman, shepherding), conversion (to milk – milk), and affixation (cowherd, stockman). The analysis reveals that many terms are historically rooted in Old English and Germanic linguistic traditions, while others have been borrowed from Latin and French, reflecting cultural and agricultural exchanges. The productivity of compounding and conversion illustrates the analytic tendency of English, where new livestock terms often emerge through semantic extension and lexical innovation rather than inflectional morphology. This typological approach highlights the dynamic nature of English livestock terminology, showing how morphology not only encodes professional knowledge but also reflects broader linguistic, cultural, and historical developments
Keywords: morphological typology; livestock terminology; English language